I costi dell’influenza in Italia - Lucioni, C.; Costa, B.; Sessa, A. (Farmeconomia. Health economics and therapeutic pathways, 2001)
The influenza is an acute viral infection that strikes respiratory tract and its diffusion is characteristic of epidemic and pandemic reoccurence. Globally the influenza represents, for the entity of its social impact (measurable in terms of morbility, hospitalization and mortality), a heavy healt care problem. In Italy the estimated incidence is 10-15%: the influenza is the third death cause for infectiuos disease, after AIDS and tubercolosis. This study is based on the Studio 606, the first italian study that allow us to pass from the presumptive phase to the observational one. The Studio 606 has been projected and realized by the Società Italiana di Medicina Generale (SIMG), involving about 200 general practitioners (MMG) in two sample region, Lombardia and Puglia. The study has been developed between December the 15th, 1998 and March the 15th, 1999. The influenza causes especially indirect costs: most of people affected with influenza doesn’t go to work for about five days and these absences create an average cost per capita of £558.000. This indirect cost represents 87% of total average cost of one single influenza event.